2009
DOI: 10.1016/j.jvs.2009.04.061
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of aortic neck length to early and late outcomes in endovascular aneurysm repair patients

Abstract: EVAR can be used for patients with a short aortic neck; however, it was associated with a significantly higher rate of early and late type I endoleaks, resulting in an increased use of proximal aortic cuffs for sealing the endoleaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 21 publications
3
126
0
4
Order By: Relevance
“…18) The suitability for EVAR is usually based on the manufacturer's IFU, which require that certain standards be fulfilled to ensure a better outcome. 19) In particular, unfavorable anatomy of the proximal aortic neck is responsible for the exclusion of about 60% of the patients who would otherwise be treated by EVAR. 18) As the indications for EVAR continue to expand, the number of patients outside of the IFU continues to grow as well.…”
Section: Discussionmentioning
confidence: 99%
“…18) The suitability for EVAR is usually based on the manufacturer's IFU, which require that certain standards be fulfilled to ensure a better outcome. 19) In particular, unfavorable anatomy of the proximal aortic neck is responsible for the exclusion of about 60% of the patients who would otherwise be treated by EVAR. 18) As the indications for EVAR continue to expand, the number of patients outside of the IFU continues to grow as well.…”
Section: Discussionmentioning
confidence: 99%
“…5) Some large studies that examined EVAR outcomes showed that the most common factors causing a poor outcome were short neck and severe neck angulation. [3][4][5] Massive neck atheroma was also shown to affect EVAR outcome when compared to the outcome of open surgery. 6) In our study, device oversizing did not occur.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies on the results of EVAR outside of IFU, aneurysmal neck factors (short length, severe angulation, and presence of massive atheroma) are commonly reported to cause EVAR-related adverse events. [3][4][5][6] Feasibility of Endovascular Abdominal Aortic Aneurysm Repair Outside of the Instructions for Use and Morphological Changes at 3 Years after the Procedure neck atheroma, even in the presence of a type 1a endoleak.…”
Section: Introductionmentioning
confidence: 99%
“…Upwards of 30% of patients with AAAs have unsuitable proximal neck morphology for conventional endovascular repair (4)(5)(6)(7). Anatomies considered unsuitable for conventional infrarenal stent grafting include short or absent necks, angulated necks, conical necks, or large necks exceeding size availability for current stent grafts.…”
Section: Technical Challengesmentioning
confidence: 99%